What underlies emotion regulation abilities? An innovative programme based on an integrative developmental approach to improve emotional competencies: Promising results in children with Prader–Willi syndrome - Famelart, Nawelle; Diene, Gwenaelle; Çabal-Berthoumieu, Sophie; Glattard, Mélanie; Molinas, Catherine; Tauber, Maithe; Guidetti, Michèle (Frontiers in Psychiatry, 2022)
Background This study aimed to test the effect of a new training programme on emotional competencies, named EMO-T, and to show the value of an integrative developmental approach. This approach postulates that the emotion regulation disturbances commonly observed in neurodevelopmental disorders are the consequence of potential disruptions in the prerequisite emotion skills. This integrative approach is particularly suitable in the case of complex and multidimensional disorders such as Prader–Willi syndrome (PWS), a rare genetic disease. Methods We examined the emotion expression, recognition, comprehension, and regulation skills in 25 PWS children aged 5–10 and 50 typically developing children (TD) aged 3–10. After a pre-test session, half of the PWS children participated in the EMO-T programme with their regular therapist for 6 weeks, while the other half continued their usual rehabilitation programme. Two post-test sessions were conducted, one at the end of the programme and one 3 months later. Results At pre-test, PWS children displayed a deficit in the four emotional competencies (EC). PWS children who participated in the EMO-T programme showed a significant and sustainable post-test improvement regarding voluntary expression and emotion recognition abilities, such that the level reached was no longer different from the baseline level of TD children. They also tended to improve in their emotion regulation, although they received no specific training in this skill. Discussion These results support that emotion regulation abilities require prerequisite emotion skills, which should be more fully considered in current training programmes. Because emotion regulation disorders strongly impact all areas of life, an integrative developmental approach appears crucial especially in the case of neurodevelopmental disorders. Further studies should be conducted to explore this perspective.